Fenretinide Acts as Potent Radiosensitizer for Treatment of Rhabdomyosarcoma Cells - Brack, Eva; Bender, Sabine; Wachtel, Marco; Pruschy, Martin; Schäfer, Beat W. (Frontiers in Oncology, 2021)
Alveolar rhabdomyosarcoma (aRMS) is a highly aggressive childhood malignancy which is mainly treated by conventional chemotherapy, surgery and radiation therapy. Since radiotherapy is associated with a high burden of late side effects in pediatric patients, addition of radiosensitizers would be beneficial. Here, we thought to assess the role of fenretinide, a potential agent for aRMS treatment, as radiosensitizer. Survival of human aRMS cells was assessed after combination therapy with fenretinide and ionizing radiation (IR) by cell viability and clonogenicity assays. Indeed, this was found to significantly reduce cell viability compared to single treatments. Mechanistically, this was accompanied by enhanced production of reactive oxygen species, initiation of cell cycle arrest and induction of apoptosis. Interestingly, the combination treatment also triggered a new form of dynamin-dependent macropinocytosis, which was previously described in fenretinide-only treated cells. Our data suggest that fenretinide acts in combination with IR to induce cell death in aRMS cells and therefore might represent a novel radiosensitizer for the treatment of this disease.